Homerus ubique: Lucian's use of Homer - Wilshere, Nicholas (2015)
It has been long acknowledged that Lucian employs various forms of allusion to the Iliad and Odyssey across his writings. This thesis builds on previous studies — which have produced taxonomic analyses of allusion, (mis)quotation and parody — to explore more fully the intertextual richness and complexity of Lucian’s writing that such approaches can paradoxically conceal.